2019
DOI: 10.37358/mp.19.2.5179
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Characterization of Polyurethane Microstructures with Propolis Extract

Abstract: Propolis is a natural apicultural product derived from plant resins with impressive health benefits. Its major biologically active substances are barely soluble in water, but this could be increased by proper formulations.The aim of the present study was to obtain a transmembrane delivery system based on polyurethane microstructures for eight propolis samples collected from different regions of Western Romania and to characterize them by differential scanning calorimetry (DSC); the assessed parameters were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…At the histopathological analysis, revised skin growth and collagen deposition at the healed wound place of the PUR-HA/1% EEP sample in comparison with other groups was observed. The obtained results showed that 1 wt.% EEP enriched PUR-HA nanofibrous can be a sanguine material with substantial biocompatibility, wound healing, and antibacterial features for next biomedical uses [38,43,44].…”
Section: Polyurethanes Modified With Antimicrobial Compoundsmentioning
confidence: 93%
“…At the histopathological analysis, revised skin growth and collagen deposition at the healed wound place of the PUR-HA/1% EEP sample in comparison with other groups was observed. The obtained results showed that 1 wt.% EEP enriched PUR-HA nanofibrous can be a sanguine material with substantial biocompatibility, wound healing, and antibacterial features for next biomedical uses [38,43,44].…”
Section: Polyurethanes Modified With Antimicrobial Compoundsmentioning
confidence: 93%